Dynamic Tensions Following New Pedagogy in Undergraduate Medical Education. (December 2019) - Daneman, Denis; Benatar, Solomon
Abstract : The authors draw on their many decades of combined experience with medical students, observing their maturation into practice in widely differing contexts, to reaffirm some of the essential goals of medical education. They briefly review curricular changes in medical education over the past 100 years, then focus on the dynamic tension in undergraduate medical education (UME) resulting from new pedagogy. Specifically, these tensions arise from the differing trajectories and directions of the 3 traditional pillars of academic medicine: clinical excellence, state-of-the-art education, and cutting-edge research. The authors highlight the role of generalism as an essential foundation of UME, as well as the dilemma of a shrinking cadre of medical students choosing a generalist career path. To address challenges stemming from pedagogical changes, the authors offer 4 observations. First, a more condensed approach to faculty development may be to ensure that bringing teachers up to speed on the new curriculum is not excessively burdensome. Second would be a more gradual introduction of the proposed changes. Third, some discussion about medical education pedagogy and curricular development ought to have a place in UME to prepare the next generation of physicians for ongoing changes in accreditation and in approaches to education. Finally, more appropriate funding of medical education would alleviate some of the burden and anxiety by acknowledging its nonmaterial value.